2015
DOI: 10.1016/j.geomorph.2015.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Physical modelling of the combined effect of vegetation and wood on river morphology

Abstract: The research reported in this paper employs flume experiments to investigate the potential effects of living vegetation and large wood on river morphology, specifically aiming to explore how different wood input and vegetation scenarios impact channel patterns and dynamics.We used a mobile bed laboratory flume, divided into three parallel channels (1.7 m wide, 10 m long) filled with uniform sand to reproduce braided networks subject to a series of cycles of flooding, wood input, and vegetation growth. Temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 47 publications
1
49
0
1
Order By: Relevance
“…A recent, pioneer experiment investigated the coupled effects of living vegetation and large wood dynamics on river morphology [Figure ; Bertoldi et al ., , Figure ]. The experiments confirmed that vegetation increases bank stability, reducing erosion, and the number of active channels [ Tal and Paola , ; Van Dijk et al ., ] and also showed how this affects large wood dynamics, promoting the formation of stable wood jams where logs accumulated constantly during sequences of floods, further increasing the effect on river morphology.…”
Section: Advances In Quantifying Large Wood Entrainment and Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent, pioneer experiment investigated the coupled effects of living vegetation and large wood dynamics on river morphology [Figure ; Bertoldi et al ., , Figure ]. The experiments confirmed that vegetation increases bank stability, reducing erosion, and the number of active channels [ Tal and Paola , ; Van Dijk et al ., ] and also showed how this affects large wood dynamics, promoting the formation of stable wood jams where logs accumulated constantly during sequences of floods, further increasing the effect on river morphology.…”
Section: Advances In Quantifying Large Wood Entrainment and Transportmentioning
confidence: 99%
“…Comparisons between (a) flume‐scale and (b) field‐scale (Tagliamento River, Italy) wood deposition patterns in a braided morphology [from Bertoldi et al , , Figure ; Used with the permission of Elsevier].…”
Section: Advances In Quantifying Large Wood Entrainment and Transportmentioning
confidence: 99%
“…Schmocker and Hager, ; Gschnitzer et al ., ). More recently, the interactions between wood and morphodynamics (Bertoldi et al ., ) and wood, vegetation, and morphodynamics (Bertoldi et al ., ) were analysed. Figure illustrates the laboratory flume at the University of Innsbruck, which has been used for experiments on LW clogging at bridges (Gschnitzer et al ., , , ).…”
Section: Physical Modelling Lw Dynamics and Related Hazardsmentioning
confidence: 99%
“…We chose to research 17 regulated streams in Lithuania: Vaišvilė (1), Dūkšta (2), Vilnoja (3), Gnesvianka (4), Ž-2 (5), Girija (6), Žalesa (7), Ž-3 (8), R-55 (9), Riešė (10), G-1 (11), Nemėža (12), Mažasis (13), Rudamina (14), N-2 (15), Asdrė (16), and Bezdonė (17 (Fig. 1).…”
Section: Study Areaunclassified
“…Thus, the streams with no overgrown woody vegetation and steeper slopes have higher probability for tides and destroying slopes. Bertoldi et al [16] agree that ensuring the stability of stream slopes and an increase in hydraulic conductivity are the two main factors that help woody vegetation make an impact on the morphometric parameters of the stream.…”
mentioning
confidence: 99%